EVALUASI PELAKSANAAN TUGAS LEMBAGA PEMBERDAYAAN MASYARAKAT DESA MAREDAN KECAMATAN TUALANG KABUPATEN SIAK - Khotami, Khotami (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
This study aims to determine the execution of tasks in the Village Community Empowerment Organization Maredan District of Tualang and constraints in the execution of tasks of the Institute for Community Empowerment in Rural Maredan District of Tualang. One Destinations shape Institute for Community Empowerment (LPM) is helping the village government in improving public services and the equitable distribution of development results by growing the initiative and to mobilize self-help mutual aid society in development. While the formulation of the problem in this research is: How Duties Institute for Community Empowerment in Rural Maredan Tualang Subdistrict Siak and any obstacles to the execution of tasks of the Institute for Community Empowerment in Rural Maredan Tualang Subdistrict Siak. Type of research is quantitative with the population of the village chief, the village secretary, village head, Chairman of RT and RW, LPM and the community with the number of respondents as many as 40 people are determined by the census and purposive sampling techniques. The data used is primary data collected through questionnaires, interviews and observations while secondary data collected through regulations, documentation, reports and other data were analyzed descriptively. Based on the analysis concluded that the implementation of the tasks Institute for Community Empowerment in Rural districts Maredan Tualang Siak considered good. It is expected that the board Institute for Community Empowerment involving all elements and different social organizations and village governments, especially the poor and women in order tewujudnya sustainable development.